Comparative transcription analysis of resistant mutants against four different antibiotics in Pseudomonas aeruginosa. (November 2021) - Zhang, Wenlu; Yuan, Yaping; Li, Shasha; Deng, Bo; Zhang, Jiaming; Li, Zhongjie
Abstract: The emergence of antibiotic resistance has severely impaired the treatment of infections caused by Pseudomonas aeruginosa . There are few studies related to comparing the antibiotics resistance mechanisms of P. aeruginosa against different antibiotics. In this study, RNA sequencing was used to investigate the differences of transcriptome between wild strain and four antibiotics resistant strains of P. aeruginosa PAO1 (polymyxin B, ciprofloxacin, doxycycline, and ceftriaxone). Compared to the wild strain, 1907, 495, 2402, and 116 differentially expressed genes (DEGs) were identified in polymyxin B, ciprofloxacin, doxycycline, and ceftriaxone resistant PAO1, respectively. After analysis of genes related to antimicrobial resistance, we found genes implicated in biofilm formation ( pelB, pelC, pelD, pelE, pelF, pelG, algA, algF, and alg44 ) were significantly upregulated in polymyxin B-resistant PAO1, efflux pump genes ( mexA, mexB, oprM ) and biofilm formation genes ( pslJ, pslK and pslN ) were upregulated in ciprofloxacin-resistant PAO1; other efflux pump genes ( mexC, mexD, oprJ ) were upregulated in doxycycline-resistant PAO1; ampC were upregulated in ceftriaxone-resistant PAO1. As a consequence of antibiotic resistance, genes related to virulence factors such as type Ⅱ secretion system ( l asA, lasB and piv ) were significantly upregulated in polymyxin B-resistant PAO1, and type Ⅲ secretion system ( exoS, exoT, exoY, exsA, exsB, exsC, exsD, pcrV, popB, popD, pscC, pscE, pscG, and pscJ ) were upregulated in doxycycline-resistant PAO1. While, ampC were upregulated in ceftriaxone-resistant PAO1. In addition, variants were obtained in wild type and four antibiotics resistant PAO1. Our findings provide a comparative transcriptome analysis of antibiotic resistant mutants selected by different antibiotics, and might assist in identifying potential therapeutic strategies for P. aeruginosa infection. Highlights: Upregulated pelB-G, algA, algF and alg44 might result in polymyxin B resistance to PAO1. Enhanced expression of mexA, mexB and oprM might contribute to ciprofloxacin resistance to PAO1. Upregulated mexC, mexD, oprJ and T3SS genes might lead to resistance and increased virulence in doxycycline resistant PAO1. The ceftriaxone resistance to PAO1 might be due to upregulated ampC.